KEPEMIMPINAN KEPALA SMP DI DAERAH TRANSMIGRASI - Putri, Mika Nusa (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to determine the leadership style of the Principals of  SMP in the Transmigration area, namely SMPN 1 and SMAN 2 Pulau Rimau, Banyuasin District. This study used a descriptive qualitative approach with multi-case study design. Data obtained by interview techniques, observation, and documentation. The technique of checking the validity of the data uses triangulation techniques. Data is analyzed by reducing data, presenting data and drawing conclusions. The results of the study, namely the first leadership style used were delegative and situational style. Second, the application of situational styles in the main tasks of the teacher, while the style of delegation in the additional tasks of the teacher in this research style must also be supplemented by good supervision by the principal. Third, the efforts of principals to improve the professionalism of teachers are by holdingpieces of trainings, conducting supervision, and evaluating and providing adequate educational facilities. Fourth, leadership barriers stem from the school's geographical conditions, low student learning motivation and lack of funding for school operations due to the small number of ASN teachers, so most BOS funds are intended to pay Honorary Teachers, and most parents of students with middle to lower economic backgrounds . Fifth, efforts to resolve obstacles are to strengthen personal relationships, improve teacher professionalism and intensive communication with committee and guardians of students.